Meningkatkan Motivasi Belajar Kebugaran Jasmani melalui Permainan Estafet untuk Siswa Kelas 5 SD Negeri Bawang 1 Kediri: Penelitian - Ayyala Haqqi Thoriq As-safa; Ardhi Mardiyanto Indra Purnomo; Mohammad Yunan Firmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Students learning motivation in learning PJOK often experiences obstacles, especially in physical fitness material. The problem is caused by learning methods that are less innovative and varied. This study aims to increase motivation to learn physical fitness through a relay game approach. This research uses the Classroom Action Research (PTK) method with the Kurt Lewin model, which consists of two cycles. Each cycle includes planning, action, observation, and reflection stages. Data were collected through observation, documentation, and questionnaires to assess students' responses to learning. The results showed a significant increase in students' learning motivation after the implementation of the relay game. In the first cycle, an average of 50.72% of students showed a positive response to PJOK learning, and in the second cycle it increased to 69.28%. From this study it can be concluded that relay games can be an effective learning method in increasing students' physical fitness learning motivation. The game-based approach is proven to be able to increase student involvement and create a more fun and interactive learning atmosphere. Therefore, teachers are advised to continue developing innovative learning methods to improve the quality of physical education.